Traveling sounds: Cairean independent music landscape. - Trzpis, Ewelina (AUC Knowledge Fountain, 2016)
The central aim of this thesis is to identify the ways in which transnational experiences of independent music artists influence their artistic performance and music production. Additionally, this work is focused on the reemergence of independent music followed by attempts at identifying the term through the discursive formations shaping its present meaning among Egyptian musicians and culturally engaged participants. This research also describes developing infrastructure of the Cairean independent music scene including detailed mapping of the 'stages' available to the independent music artists.